Revisiting the significance of right bundle branch block. (25th November 2020) - Nakazawa, N; Ishizu, T; Sairenchi, T; Sato, K; Yamamoto, M; Machino, T; Murakoshi, N; Kawakami, Y; Ieda, M
Abstract: Background/Introduction: The right bundle branch block (RBBB) has been considered a benign finding in asymptomatic individuals. However, this concept based on a few, old, small sample size studies. Recently, the importance of the right ventricular dysfunction was focused on cardiovascular prognosis in clinical cardiology. Purpose: To determine the prognostic value of RBBB in community-based health checkups cohort with a large sample size in recent years in Japan. Methods: We assessed 88, 089 individuals (mean age, 58.3±10.2 years; 66.1% women) who participated in annual community-based health checkups. Exclusion criteria were current or previous history of heart disease, stroke, and intraventricular block such as left bundle branch block other than RBBB. We followed them from 1993 to 2016. The primary endpoint was cardiovascular death, or all-cause death. The Cox regression model was assessed in each gender. The variables included in the multivariate analyses were age, body mass index, systolic blood pressure, hypertension, total cholesterol level, high-density lipoprotein cholesterol level, treated-hyperlipidemia, hyperglycemia, treated-diabetes, estimated glomerular filtration rate (eGFR), current smoking, and drinking habit. Results: The prevalence of RBBB was higher in men than women (723/29, 863 2.4% in men vs. 581/58, 204 1.0% in women, P<0.001). In both genders, subjects with RBBB were significantly older and had higher systolic blood pressure and lower eGFR compared with individuals without RBBB. In women, RBBB was associated with significantly increased cardiovascular mortality with multivariate-adjusted hazard ratios (HR) of 1.26 [95% confidence interval (CI), 1.03–1.54]. Then, we divided them into younger or elder groups according to the cut-off age of 65-year-old. In women ≤65-year-old, RBBB related to greater cardiovascular mortality with multivariate-adjusted HR of 1.89 [95% CI, 1.27–2.80]. However, in women >65-year-old, RBBB did not show the prognostic significance. In men, RBBB did not reach the significant results in all participants, however, men >65-year-old with RBBB showed the significant poor prognosis with HR of 1.26 [95% CI, 1.04–1.53]. Conclusions: In this cohort study, contrary to common perception, RBBB was associated with increased cardiovascular mortality in women, especially younger women ≤65-year-old, and elderly men. To the extent we know, the present study is the largest and long-term follow-up study showing that the significance of RBBB differs depending on sex and age. Especially in young women who usually are less prone to show wide QRS, RBBB might represent the pathological abnormality. Although the pathophysiological effect of the RBBB on the cardiovascular outcome needs further investigation in the future, clinicians should alert the RBBB in young women and elder men even if they have no symptoms and evaluate the heart abnormality and follow them up carefully. Funding Acknowledgement: Type of funding source: None